Pemberdayaan Pelaku Usaha Kepeng Dan Krupuk Ikan Melalui Pelatihan Pengemasan Dan Pemasaran Produk Olahan Lokal Di Desa Padike, Talango Sumenep-Madura - Sutrisno, Tri (Institut Agama Islam Negeri (IAIN) Kudus, 2025)
Empowerment Of Kepeng And Fish Cracker Business Actors Through Training In Packaging And Marketing Of Local Processed Products In Padike Village, Talango Sumenep-Madura. This community service activity aims to empower local food-processing entrepreneurs producing kepeng and fish crackers in Padike Village, Talango District, Sumenep Regency through packaging and marketing training. Based on the initial identification, business actors in the village still face various limitations, particularly in packaging design, promotional strategies, and product legality. In fact, the potential of local raw materials and skills is highly promising for development into more economically valuable enterprises. This program was implemented using the Asset-Based Community Development (ABCD) approach, which emphasizes exploring and utilizing local potential through five stages: discovery, dream, design, define, and destiny. The activities were carried out on 14–19 April 2025 and involved 15 local entrepreneurs. The results show that participants experienced significant improvements in technical skills and marketing strategies. Approximately 80% of participants began packaging their products with attractive labels and started marketing them digitally. Social impacts were also evident, including the establishment of a joint business initiative and increased self-confidence among entrepreneurs to compete in markets beyond the village. The ABCD approach successfully fostered collaborative and participatory spirit, forming a foundation for program sustainability. The conclusion of this activity indicates that local potential–based training using a participatory approach can enhance the capacity of household businesses both technically, socially, and economically